Fluorescence‐activated cell sorting (FACS) of osteoblasts and osteoclasts for RNA sequencing in a medaka, Oryzias latipes (Temming & Schlegel, 1846), osteoporosis model. (2nd March 2018) - Buettner, A.; Sundaram, S.; Vyas, H.; Yu, T.; Mathavan, S.; Winkler, C.
Summary: Transcriptome profiling of selected cells involved in bone formation, degeneration and repair provides novel insight into mechanisms of bone cell coupling and homeostasis. A medaka osteoporosis model was reported earlier, where excess bone resorption is triggered by induction of receptor activator of nuclear factor κB ligand (RANKL) expression, and bone cell behaviour visualized by live imaging. Herein a protocol for fluorescence‐activated cell sorting (FACS) is described that allows isolation of distinct bone cell types from larvae for subsequent RNA sequencing to detect molecular changes during different phases of bone degeneration and repair.